2016
DOI: 10.1504/ijbex.2016.073375
|View full text |Cite
|
Sign up to set email alerts
|

The use of the balanced scorecard in bank strategic management

Abstract: In this study, we employ 'step-by-step' algorithm for constructing a strategy map of the balanced scorecard (BSC) for banking institutions using the example of one of the Russian regional banks. The key evaluation indicators of banking performance are selected through the relevant literature analysis while considering the peculiarities of a sample bank. Further, the decision making trial and evaluation laboratory (DEMATEL) method is employed in order to identify causal relationships between the KPIs, i.e., dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…On the other hand, Balkovskaya and Filneva (2016) constructed a strategic approach of the BSC for banking organizations using a Russian regional bank as an example. They found that the efficiency of transactions, sales development, and efficient procedures are three significant aspects that should be enhanced as they have a strong effect on the performance of the bank.…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the other hand, Balkovskaya and Filneva (2016) constructed a strategic approach of the BSC for banking organizations using a Russian regional bank as an example. They found that the efficiency of transactions, sales development, and efficient procedures are three significant aspects that should be enhanced as they have a strong effect on the performance of the bank.…”
Section: Literature Reviewmentioning
confidence: 99%
“…(3) Link financial goals. Balkovskaya and Filneva [52] took one of the regional banks in Russia as an example, constructed a balanced scorecard (BSC) strategy map for banking institutions, and selected key evaluation indicators for bank performance through relevant literature analysis. They then used an objective method to determine the causal relationship between KPIs, that is, the direction and intensity of their mutual influence, and defined the most strategically significant indicators, which could help managers determine the priority of their strategic steps within the limited resources so as to view the strategy of their bank in the most effective way.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Lucie and Iveta [56] and Lucas, Sandra Mara, Vinicius, and Sandra [85] also support this view. Balkovskaya and Filneva [52] constructed a balanced scorecard strategy map for banking institutions, and they pointed out that it can help managers prioritize their strategic steps within limited resources so that they can browse their bank's strategy. Therefore, this study uses the BSC as the performance evaluation method for the catering industry and the credit card issuing bank marketing alliance.…”
Section: The Combining Of Fuzzy Ahp and Balance Scorecardmentioning
confidence: 99%
“…Therefore, its accomplishment needs to be evaluated by a holistic model to sustain the bank (Wu, Tzeng, & Chen, 2009). One of the assessment methods of performance used in this research is the balanced scorecard (BSC) (Kaplan & Norton, 1992), which can also be applied to banks [see Davis and Albright (2004), Kim and Davidson (2004), Balkovskaya and Filneva (2016), Wu et al (2019)]. According to Davis and Albright (2004) and Lawrie and Cobbold (2004), BSC is an evaluating tool for extensive and universal performance to plan and control an organization to achieve its goals.…”
Section: Introductionmentioning
confidence: 99%